Experimental and theoretical investigation of the tuning of electronic structure in SnO2via Co doping for enhanced styrene epoxidation catalysis. Issue 5 (3rd February 2022) - Liu, Jiangyong; Ji, Xingyang; Shi, Jie; Wang, Lixia; Jian, Panming; Yan, Xiaodong; Wang, Dan
Abstract : Co doping is an effective strategy for the tuning of electronic structure in SnO2, which leads to a huge boost in the styrene epoxidation reaction performance. Abstract : Exploiting new heterogeneous catalysts composed of earth-abundant elements for various organic transformations under moderate reaction conditions is of vital importance in modern synthetic chemistry. Herein, we report an effective strategy for the tuning of electronic structure in SnO2, which leads to a huge boost in the styrene epoxidation reaction (SER) performance. Combined experimental and theoretical analyses highlight the validity of Co doping strategy in the manipulation of the electronic structure of SnO2 to achieve the decrease of oxygen vacancy (OV) formation energy, modulation of Sn valence state and adjustment of Sn–O interactions. The Sn 2+ –OV–Co–O species are proposed as the active sites, contributing to the activation of tert -butyl hydroperoxide and coordination of styrene. This work serves as a guideline for the performance enhancement of selective oxidation of aromatics via introducing hetero-atom doping strategy in the metal oxide catalyst system.